Democratic Republic of Sao Tome and Principe : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2005)
This Joint Staff Advisory Note focuses on the Poverty Reduction Strategy Paper (PRSP) for the Democratic Republic of Sao Tome and Principe. The PRSP sets an ambitious policy agenda-with an overall cost of about USD 210 million for the first seven years of implementation. It provides a reliable framework for reducing poverty in Sao Tome and Principe. It identifies women, the elderly, and the young in need of special support, and envisages improving the access of women and the young to literacy programs and occupational training.